PERBEDAAN KARAKTERISTIK BALITA STUNTING DI PEDESAAN DAN PERKOTAAN TAHUN 2017 (Studi Pada Anak Usia 24-59 Bulan di Wilayah Kerja Puskesmas Gabus II dan Wilayah Kerja Puskesmas Pati II Kabupaten Pati) - Aprilliyani Pepi Lusita; Suyatno Suyatno; M. Zen Rahfiludin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Linear growth failure is the most common form of undernutrition globally. Indonesia ranks fifth in the world for the number of stunting. Stunting is suffered by approximately 8 million children in Indonesia. Some studies show that the prevalence rate of stunting among under-5 children is much higher in rural areas than urban areas. The purpose of this study was to compare the characteristics stunting among under five children in the rural and urban. Type of this study is an explanatory research method and cross-sectional design with sample sixty eight respondents in rural and urban area of Pati regency, central java. Normality test using Kolmogorov-Smirnov and analyzed using independent t-test and Mann-Whitney with α = 0.05. The results showed that the characteristics stunting among under five children in the rural and urban area have a significant differences include mother's education (p = 0.001), the level of mother’s knowledge about nutrition (p = 0.014), duration of the upper respiratory tract infection (p=0.018). While the characteristics stunting among under five children in the rural and urban area did not have a significant differences include age of children (p=0,941), sex of children (p=0,051), Z-score of children (p=0,127), the mother’s job (p = 0.145), economic status (p = 0.487), the frequency of upper respiratory tract infection (p = 0.797), duration of diarrhea (p = 0.799), frequency of diarrhea (p = 0.824), the level of energy consumption (p = 0.816) and the level of protein consumption (p = 0.065). Conclusion : the characteristics stunting among under five children in the rural and urban area have a significant differences are include mother's education, the level of mother’s knowledge about nutrition and duration of the upper respiratory tract infection. Suggestion : to increase the mother’s knowledge about nutrition especially in rural areas.